Alteronol Enhances the Anti-tumor Activity and Reduces the Toxicity of High-Dose Adriamycin in Breast Cancer - Ren, Boxue; Ye, Lei; Gong, Jianwei; Ren, Huanhuan; Ding, Yangfang; Chen, Xiaoyu; Liu, Xiaona; Lu, Peng; Wei, Fei; Xu, Wenjuan; Zheng, Qiusheng; Li, Defang (Frontiers in Pharmacology, 2019)
The first-line chemotherapy drug adriamycin (ADM) is widely used for the treatment of breast cancer, but the acquired drug resistance and the normal tissue toxicity remain clinical challenges. Alteronol has been reported to has a widespread anti-tumor activity. In this study, we firstly examined the synergistic anti-tumor effects and its underlying mechanism of alteronol combined with ADM in breast cancer. We have found that the combination of alteronol and ADM significantly suppressed the protein expression of cell cycle-related molecules (CDC2 and CyclinB1) and induced cell cycle arrest at G2/M phase, leading to cell proliferation inhibition in breast cancer 4T1 cells. Moreover, co-treatment of alteronol and ADM remarkably activated p38 and JNK kinases, elevated ROS level and triggered mitochondrial dysfunction, then released cytochrome c and up-regulated apoptotic related proteins, e.g. cleaved PARP, Bax, Bcl-2 and cleaved caspase-3/9, followed by cell apoptosis. Furthermore, the in vivo study showed that the low-dose combination of alteronol (2 mg/kg) and ADM (1 mg/kg) significantly inhibited the tumor growth in the tumor-bearing mice, and the antitumor effect of the combination was the same as the antitumor effect of high-dose ADM (8 mg/kg). In addition, the low-dose combination group showed less toxicities to major organs than that in high-dose ADM group. Taken together, these data demonstrated that the low-dose combination of alteronol and ADM could notably improve the antitumor activity and reduce the toxicity of high-dose ADM.